The Influence Attitudes, Subjective Norms And Perceptions Behavioral Control Of Depok Community Interest In Sharia Card Ownership - fajrianti, lutfiah (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2023)
This study aims to examine the influence of attitude factors, subjective norms and perceptions of behavioral control on interest in sharia card ownership by taking a case study in the city of Depok. This research is a quantitative research. Data was obtained by distributing questionnaires online with 110 respondents from Depok City. The sampling technique used in this study is non-probability sampling, Partial Least Square (PLS) is used as a data analysis technique and uses SmartPLS 3.0 software. Based on the results of data analysis, the perceived factor of behavioral control has a significant positive effect on interest in sharia card ownership, while attitudinal factors and subjective norms do not have a significant positive effect on interest in sharia card ownership. So that attitudes and subjective norms are not a strong factor in deciding to have a sharia card. recommendations for further research should be to develop research by adding other factors or variables that have not been studied in this research, such as perceived usefulness, perceived religiosity and perceived convenience so that it can strengthen the concept for further research which discusses the factors that influence interest in using sharia . card and it is also hoped that future researchers will expand the research object.